Studi Komparatif Konsep Nabi Dan Kenabian Agama Islam Dan Kristen Mormon - M. Riyan Hidayat; Nurun Nissa Baihaqi; Najamuddin Najamuddin; Mahfidhatul Khasanah; Aidah Mega Kumalasari (Al Hikmah, 2021)
ABSTRACT :This study focuses on two main points of the problem, namely how the concept of prophethood according to religions and how the comparison between the concept of prophethood in Islam and Mormon Christianity. As for this type of research, it is library-based, while the method of collection is by using the documentation method. The results of this study indicate that there are significant differences and similarities between these two religions. His similarities reveal that the Prophet was not an ordinary human being, he was appointed as the representative of God, he was assigned to bring news to mankind, acknowledged other Prophets. Among the differences lies in the Mormon belief that the prophet is unbroken, the congregation is free to choose the prophet, apostasy for those who reject the prophet and the concept of the restoration of the church as the key to prophethood. While Islam believes that the Prophet is the last messenger, all Prophets are chosen by God, the rejection of the Prophet is not to the degree of apostasy and there is no concept of restoration as the restoration of the Mormon Christian church.Keyword: Comparative Studies, Prophetic, Christian Mormon ABSTRAK :Penelitian ini berfokuskan pada dua titik pokok permasalahan yakni bagaimana konsep kenabian menurut agama-agama dan bagaimana perbandingan antara konsep kenabian dalam Islam dan Kristen Mormon. Adaapun jenis penilitian ini berbasis pustaka sedangkan metode pengumpulannya yakni dengan menggunakan metode dokumentasi. Hasil penelitian ini menunjukkan pada perbedaan dan persamaan yang cukup signifikan diantara dua agama ini. Persamaan nya mengungkap bahwa Nabi bukanlah manusia biasa, ia ditunjuk sebagai wakil Tuhan, ia ditugaskan untuk membawa berita kepada umat manusia, mengakui Nabi lain. Diantara perbedaannya terletak pada pada keyakinan mormon bahwa nabi itu tak terputus, jemaat bebas memilih Nabi, murtad bagi yang menolak Nabi dan konsep pemulihan gereja sebagai kunci kenabian. Sedangkan Islam meyakini Nabi adalah utusan terakhir, semua Nabi dipilih oleh Allah, penolakan terhadap Nabi tidak sampai derajat murtad dan tidak adanya konsep pemulihan sebagaimana pemulihan geraja kristen Mormon.Kata Kunci : Studi Komparatif, Kenabian, Kristen Mormon